The Effects of the Real Oil Price on Regional Wage Dispersion - Matthias Kehrig; Nicolas L. Ziebarth (Center for Economic Studies and ifo Institute (CESifo), 2017)
We find that oil supply shocks decrease average real wages, particularly skilled wages, and increase wage dispersion across regions, particularly unskilled wage dispersion. In a model with spatial energy intensity differences and nontradables, labor demand shifts, while explaining the response of average wages to oil supply shocks, have counterfactual implications for the response of wage dispersion. Only an additional response in labor supply can explain this latter fact highlighting the importance of general equilibrium effects in a spatial context. We provide additional empirical evidence of regionally directed worker reallocation and housing prices consistent with our spatial model. Finally, we show that a calibrated version of our model can quantitatively match the estimated effects of oil supply shocks.
Keywords: E24; J24; J31; J61; 330; wage dispersion; labor reallocation; skill heterogeneity; oil prices